Evaluation of a multiplex real-time PCR panel for the diagnosis of intestinal helminths - N. F. J. Schillaci; M. Cuntrò; E. Oliva; L. Clemente; S. Varani; N. Menegotto; V. Besutti; A. Bruno; L. Petrullo; D. Oggioni; A. Carducci; C. Ghia; et al. (Microbiologia Medica)
Not available.